Edge of Empire: The Civilizing Mission of Adult Education in Vancouver and Early British Columbia, 1858-1918 - Ian Hunt (Adult Education Research Conference, 2000)
Throughout the British Empire, an educational mission was established under imperialism's patronage, to study and categorize the new world, and to bring civilization and culture to the colonies. Nineteenth and early 20th century British Columbia was no exception. The civilizing mission of colonizers was to bring to British Columbia some of the finest of British and European cultural sensibilities--to make British Columbia British.